Pengalaman Guru Pendidikan Agama Islam Dalam Mengimplementasikan Metode Pembelajaran Disekolah Dasar - Fernanada, Eliza; Marpaung, Eridawati; Siregar, Pani Akhiruddin (Journal of Sustainable Education, 2025)
Abstract: This study aims to describe the experiences of Islamic Religious Education (PAI) teachers in implementing teaching methods at the elementary school level. Utilizing a qualitative approach with a phenomenological framework, this research analyzes the perceptions, challenges, and adaptations made by teachers in their teaching methods. Data were collected through in-depth interviews and participatory observations of five PAI teachers in elementary schools in region X. The findings indicate that teachers apply contextual and interactive approaches to address limitations in facilities and the diverse characteristics of students. This study provides practical contributions to the development of innovative and adaptive PAI teaching methods in elementary schools. Additionally, it identifies several challenges faced by teachers, including a lack of resources and support from educational institutions. The findings contribute to the development of more effective PAI teaching methods at the elementary school level and offer recommendations for policymakers to enhance the quality of religious education in schools. This research is expected to serve as a reference for future studies and assist teachers in improving their teaching practices.